DYNAMICS OF MELTING OF ACIDIC VOLCANIC PRODUCTS IN CONTACT WITH MAFIC DIKES (ON KUNASHIR ISLAND) - Litvinovskiy B.A.; Podladchikov Y.Y. (My University, 1989)
There exists an enormous literature on the evolution of acidic magmas in the zone of contact of sialic rocks with intruded mafic melts. It is generally thought that the resulting contact melting is likely to be important only at medium or great depths. In the present paper the authors describe contact melting at shallow depths which can occur if the sialic rocks have a high water content. The same phenomenon has also been described for Itsu Island in central Japan They investigated Cenozoic volcanic and subvolcanic rocks in Kunashir Island Kurile Arc). The Middle Pleistocene silicic volcanic rocks here commonly contain dikes of tholeiitic basalt, andesite. In some cases, the silicic rocks underwent melting at the contact with the dikes.
Keywords: Cenozoic; Pleistocene; Кайнозой; Cenozoic::Quaternary::Pleistocene; Cenozoic; Кайнозой::Четвертичная::Плейстоцен